Management of carbapenem-resistant Enterobacteriaceae infections. (August 2019) - Durante-Mangoni, E.; Andini, R.; Zampino, R.
Abstract: Background: Carbapenem resistance is defined as in vitro non-susceptibility to any carbapenem and/or documented production of a carbapenemase. This feature has rapidly spread worldwide among clinical isolates of Enterobacteriaceae, mostly Klebsiella spp., and is associated with diverse molecular mechanisms. Carbapenem resistance is often associated with resistance to all traditional β-lactams and other classes of antibiotics, denoting a typical example of an extensively drug-resistant phenotype. Objectives: To summarize and interpret in a balanced manner the most clinically relevant data in terms of carbapenem-resistant Enterobacteriaceae (CRE) infection management. Sources: Data were extracted by PubMed and clinicaltrials.gov search and manual scrutiny among references of analysed articles. Content: Features of newer and older, rediscovered antimicrobial options for CRE are described. Observational studies and randomized clinical trials (RCT) of CRE treatment are summarized, with a specific focus on the effects of monotherapy compared with combination treatment. Implications: The available evidence on the current management of CRE mostly comes from observational, non-comparative, retrospective, small studies, with a high risk of selection bias. Very little evidence comes from RCT. Conflicting results of RCT and observational studies call for caution before combination therapies are deemed superior to monotherapy. Data on newer agents have spurred enthusiasm but remain limited as concerns severe CRE infections. A balanced approach should guide the clinician in the choice of old or new drugs, and of monotherapies or combination regimens. Efforts should be made to perform adequately sized clinical trials answering well-defined research questions.